Effects of GW274150, a novel and selective inhibitor of iNOS activity, in acute lung inflammation - Dugo, Laura (2004)
1. The aim of this study was to investigate the effect of GW274150, a novel, potent and selective inhibitor of inducible nitric oxide synthase (iNOS) activity in a model of lung injury induced by carrageenan administration in the rats. 2. Injection of carrageenan into the pleural cavity of rats elicited an acute inflammatory response characterized by: fluid accumulation in the pleural cavity which contained a large number of polymorphonuclear cells (PMNs) as well as an infiltration of PMNs in lung tissues and subsequent lipid peroxidation, and increased production of nitrite/nitrate (NO(x)), tumour necrosis factor α (TNF-α) and interleukin-1β (IL-1β). 3. All parameters of inflammation were attenuated in a dose-dependent manner by GW274150 (2.5, 5 and 10 mg kg(−1) injected i.p. 5 min before carrageenan). 4. Carrageenan induced an upregulation of the intracellular adhesion molecules-1 (ICAM-1), as well as nitrotyrosine and poly (ADP-ribose) (PAR) as determined by immunohistochemical analysis of lung tissues. 5. The degree of staining for the ICAM-1, nitrotyrosine and PAR was reduced by GW274150. These results clearly confirm that NO from iNOS plays a role in the development of the inflammatory response by altering key components of the inflammatory cascade. 6. GW274150 may offer a novel therapeutic approach for the management of various inflammatory diseases where NO and related radicals have been postulated to play a role.